Development of an innovative sub-surface stormwater control system - Ghazali, Abdul Halim; AL-Hamati, Abdullah Ali Nassir; Mohammed, Thamer Ahmed; Noorzaei, Jamaloddin (Faculty of Design & Architecture, Universiti Putra Malaysia, 2009)
Flooding and pollution due to increase in the impervious areas as a result of urbanization are common problems. Several stormwater control systems were developed to reduce the effect of urbanization on the quantity and quality of stormwater runoff. Systems installed in sub-surface have the potential of being used in developed areas where land cost and/ or availability are major concerns. A new competitive sub-surface stormwater retention system was developed and called the Storage-Infiltration Block (SIB) system. Modeling of the SIB system using finite element technique was performed to improve its configuration design and to evaluate its structural capability under the design load. The structural and hydraulic performance of the system was evaluated experimentally based on laboratory models. In this paper a description of the SIB system, its performance, advantages, and the applications will be briefly discussed. Furthermore, an overview of the SIB system designer which is a computer program developed to facilitate the design of the system will be presented in this paper